Diabetes Self-Management Education; Experience of People with Diabetes - Mardanian Dehkordi, Leila (J Caring Sci, 2017)
Introduction: Diabetes self-management education (DSME) is a major factor which can affects quality of life of people with diabetes (PWD). Understanding the experience of PWD participating in DSME programs is an undeniable necessity in providing effective DSME to this population. The Aim of the study was to explore the experiences of PWD from a local DSME program in Iran. Methods: This study applied a descriptive phenomenological approach. The participants were PWD attending a well-established local DSME program in an endocrinology and diabetes center in Isfahan, Iran. Fifteen participants willing to share their experience about DSME were selected through purposive sampling from September 2011 to June 2012. Data were collected via unstructured interviews and analyzed using Colaizzi's approach. Results: The experience of participants were categorized under three main themes including content of diabetes education (useful versus repetitive, intensive and volatile), teaching methods (traditional, technology ignorant) and learning environment (friendly atmosphere, cramped and dark). Conclusion: It seems the current approach for DSME cannot meet the needs and expectations of PWD attending the program. Needs assessment, interactive teaching methods, multidisciplinary approach, technology as well as appropriate physical space need to be considered to improve DSME.